Core outcome measures for research in traumatic injury survivors: The National Trauma Research Action Plan modified Delphi consensus study. Issue 5 (25th May 2022) - Herrera-Escobar, Juan Pablo; Price, Michelle A.; Reidy, Emma; Bixby, Pamela J.; Hau, Kaman; Bulger, Eileen M.; Haider, Adil H.; ,
Abstract : As part of the National Trauma Research Action Plan, we conducted a modified Delphi consensus study to identify and prioritize a set of core outcome domains and measures that will facilitate the synthesis, comparison, and interpretation of long-term trauma outcomes research. Abstract : BACKGROUND: Until recently, survival has been the main outcome measure for injury research. Given the impact of injury on quality of life, the National Academies of Science, Engineering, and Medicine has called for advancing the science of research evaluating the long-term outcomes of trauma survivors. This is necessary so that treatments and interventions can be assessed for their impact on a trauma patients' long-term functional and psychosocial outcomes. We sought to propose a set of core domains and measurement instruments that are best suited to evaluate long-term outcomes after traumatic injury with a goal for these measures to be adopted as a national standard. METHODS: As part of the development of a National Trauma Research Action Plan, we conducted a two-stage, five-round modified online Delphi consensus process with a diverse panel of 50 key stakeholders including clinicians, researchers, and trauma survivors from more than 9 professional areas across the United States. Before voting, panelists reviewed the results of a scoping review on patient-reported outcomes after injury and standardized information on measurement instruments following the Consensus-based Standards for the Selection of Health Measurement Instruments guidelines. RESULTS: The panel considered a preliminary list of 74 outcome domains (patient-reported outcomes) and ultimately reached the a priori consensus criteria for 29 core domains that encompass aspects of physical, mental, social, and cognitive health. Among these 29 core domains, the panel considered a preliminary list of 199 patient-reported outcome measures and reached the a priori consensus criteria for 14 measures across 13 core domains. Participation of panelists ranged from 65% to 98% across the five Delphi rounds. CONCLUSION: We developed a core outcome measurement set that will facilitate the synthesis, comparison, and interpretation of long-term trauma outcomes research. These measures should be prioritized in all future studies in which researchers elect to evaluate long-term outcomes of traumatic injury survivors. LEVEL OF EVIDENCE: Diagnostic Test or Criteria, Level IV. Abstract :